Soil classification and prediction model for critical land on the slopes of Mount Raung in Indonesia - Basuki, Basuki; Anggriawan, Rendy; Sari, Vega Kartika; Rohman, Fahmi Arief (Brawijaya University, 2024)
Indonesia is in the ring of fire, which has an impact on the characteristics of volcanoes, one of which is Mount Raung. Mount Raung, part of the Iyang-Argopura mountains, has a role in influencing the development of soil types and the environment; it was recorded in 1586, 1987, 1597, and 1638. Soil types and environmental parameters have an influence on critical land conditions. Remote sensing technology has been used in various fields, one of which is land evaluation. This study examined the distribution of soil characteristics and the mapping of critical lands through remote sensing approaches. The method used to identify the morphological characteristics of soil classification and the potential for critical land was a descriptive-exploratory method. The results of the research on soil types are divided into three orders, namely Andisols, Inceptisols, and Alfisols. The three land orders are divided into nine great groups, with Lithic Eutrudepts having the highest area of 38.02%, followed by Typic Hapludalfs (21.70%), Typic Eutrudepts (9.79%), Typic Epiaquepts (7.84%), Aquic Eutrudepts (7.71%), Aquic Eutrudepts (5.64%), Fluventic Epiaquepts (5.30%), Typic Udivitrands (2.16%), and Vitric Hapludands (1.83%). Critical land based on the analysis of five factors of erosion, land use, slope, rainfall, and soil canopy density, is divided into four criteria i.e., critical area of 895.88 ha, medium critical 9,027.69 ha, and lightly critical of 14,096.89 ha. Land use, slope, and plant canopy density play a major role in the potential for critical land with a strong-very-strong level of closeness (0.350-0.610).